Tuberculosis Vaccines – state of the art, and novel approaches to vaccine development. (March 2015) - da Costa, Christopher; Walker, Barry; Bonavia, Aurelio
Highlights: The increasing global incidence of tuberculosis, including multi- and extensively-drug resistant disease, calls for renewed efforts to develop a safe and effective vaccine Several new candidate vaccines are currently in preclinical stage development, with evaluation of novel approaches to vaccine delivery Experimental medicine studies in human and non-human primate models of tuberculosis provide the potential for decreasing the time and cost of developing new vaccines, with increasing chances of late stage success There is currently a wealth of promising candidate vaccines also in various phases of clinical development Summary: The quest for a vaccine that could have a major impact in reducing the current global burden of TB disease in humans continues to be extremely challenging. Significant gaps in our knowledge and understanding of the pathogenesis and immunology of tuberculosis continue to undermine efforts to break new ground, and traditional approaches to vaccine development have thus far met with limited success. Existing and novel candidate vaccines are being assessed in the context of their ability to impact the various stages that culminate in disease transmission and an increase in the global burden of disease. Innovative methods of vaccine administration and delivery have provided a fresh stimulus to the search for the elusive vaccine. Here we discuss the current status of preclinical vaccine development, providing insights into alternative approaches to vaccine delivery and promising candidate vaccines. The state of the art of clinical development also is reviewed.